Twitter: An opportunity or a curse for South African female journalists? - Gambade, Emilie (Centre for Film and Media Studies, 2023)
The spread of cyberviolence around the globe and cyberbullying towards female journalists is growing (Mijatović, 2016); in fact, thanks to improved technology and the proliferation of bots and botnets (Barojan, 2018), it is becoming even more ubiquitous. The cruelty and frequency of the attacks prompted UN Secretary-General António Guterres to declare in March 2021: “There should be no room for misogyny and violence in journalism. Social media platforms and governments must protect women journalists from online violence” (Posetti et al, 2021.) However, social media companies, government bodies and regulators have done little to curb the toxicity of the discourse often held on social media platforms, the violence of attacks and cyberviolence in general. In South Africa, Twitter had “9.3 million users in 2021… up 4% from 2020” (Staff Writer, BusinessTech, 2021.) However, the number of intimidations and threats towards female journalists also increased, especially on Twitter (Quintal, 2019). This essay serves as research material for the short film ‘Section 16', which is also submitted for the completion of a Master's degree in Documentary Arts. It features interviews with selected female journalists working at Daily Maverick, who through personal accounts and specific experiences describe why they use Twitter, even though they are or might be subject to online violence (Anonymous, personal communication, August 2021.) They understand the dilemma many journalists face in today's connected world: on the one hand, Twitter provides leads to stories, work opportunities and global news alerts (Anonymous, personal communication, August 2021); on the other hand, it also puts the user at risk of emotional abuse, ‘loneliness and possible trauma' (Daniels & Lowe Morna, 2018.) This dissertation also studies, as a foundation for the film ‘Section 16', the extent and frequency of usage, the type of content shared and the level of engagement, and explores the impact of Twitter, from the time they started using the platform to the present day, and the feelings and emotions using the platform sparks. Findings show that “the hate machine” (Simon, 2021) and online violence directly influence and curb journalists' interactivity on the platform, even if only a little, as usage becomes more carefully controlled and at times constrained; the bigger a journalist's Twitter following, the more important the platform is within and for their work – regardless of the emotional toll that using the platform has on them (Anonymous, personal communication, August 2021.) Furthermore, an experienced journalist I spoke to who worked in a newsroom during apartheid explained that they found social media violence not dissimilar to what they experienced in the years leading to the release of Nelson Mandela and the first democratic national elections on 27 April 1994 (Anonymous, personal communication, August 2021.) This research and the findings helped considerably in further developing interview questions, structuring the storyline of the film ‘Section 16', finding the arc of the film's narrative and editing the final cut.